DEVELOPMENT OF COMBINED MODULE USING CONTEXTUAL SCIENTIFIC APPROACH TO ENHANCE STUDENTS' COGNITIVE AND AFFECTIVE - Muhamad Yusup Kurniansyah; Wahyu Hidayat; Euis Eti Rohaeti (Jurnal Infinity, 2022)
This research on the development of experimental product test designs aims to develop learning products to solve problems that occur in the field and find out and analyze the mathematical problem-solving abilities and Habits of Mind of MTs students whose learning uses a combination of scientific approaches and contextual approaches compared to MTs students who use scientific approaches. The research subjects were conducted on students in Indonesia with details of 1 class at MTs Azzahra Batujajar for a limited trial, three classes from MTs Bhakti Pertiwi Cililin, MTs Albidayah, and MTs Al-Mukhtariyah Rajamandala for field trials, and two classes at MTs Nurul Hidayah Batujajar for product testing and used as the experimental class and the control class. The instrument in this research is a set of mathematical problem-solving abilities and a non-test to determine the students' Habits of Mind. The results of this study indicate that the process of developing teaching materials is carried out well, and the product is feasible to use. Mathematical problem-solving abilities and Habits of Mind of students who receive learning using a combination of scientific and contextual approaches are better than those who receive knowledge using a scientific approach.